2006
DOI: 10.1002/jez.a.256
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical targeting of sea anemone cytolysins on tentacles, mesenteric filaments and isolated nematocysts ofStichodactyla helianthus

Abstract: The toxicity of biomolecules obtained from sea anemones in vitro does not necessarily justify their function as toxins in the physiology of the anemone. That is why anatomical and physiological considerations must be taken into account in order to define their physiological role in the organism. In this work, antibodies generated to Sticholysin II, a cytolysin produced by the Caribbean Sea anemone Stichodactyla helianthus, are used as specific markers to explore the sites of production and storage of the cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 11 publications
0
35
0
2
Order By: Relevance
“…Actinoporins have not been identified in nematocysts [56,63], although genetic components (signal peptide and propart motif) indicate that they are likely synthesized in the Golgi apparatus during nematocyst development [15,64]. Additionally, tissue-specific studies have shown that actinoporins are expressed in mesenterial filaments, suggesting that they play a role in digestion [65]. Despite most prey or predator species having a relatively conserved and ubiquitous actinoporin target site (sphingomyelin), many highly conserved actinoporins exhibit variable rates of cytolytic activities [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinoporins have not been identified in nematocysts [56,63], although genetic components (signal peptide and propart motif) indicate that they are likely synthesized in the Golgi apparatus during nematocyst development [15,64]. Additionally, tissue-specific studies have shown that actinoporins are expressed in mesenterial filaments, suggesting that they play a role in digestion [65]. Despite most prey or predator species having a relatively conserved and ubiquitous actinoporin target site (sphingomyelin), many highly conserved actinoporins exhibit variable rates of cytolytic activities [40].…”
Section: Discussionmentioning
confidence: 99%
“…Despite most prey or predator species having a relatively conserved and ubiquitous actinoporin target site (sphingomyelin), many highly conserved actinoporins exhibit variable rates of cytolytic activities [40]. This suggests that minor changes in amino acids across actinoporins may have co-diversified to target cell membranes in specific lineages [8,15,41,65,66]. There is still much to be done to understand how these venoms function in an ecological and evolutionary context.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, given that binding appears unaffected, differences in haemolytic activity would have been negligible. However, since the natural targets of these proteins do not seem to be mammalian erythrocytes, but instead some small fishes or crustaceans , the possibility for the RGD sequence motif being also involved in binding to some integrin‐like receptor when encountering the right prey cannot be discarded by the results presented now.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, binding of these proteins to SM is so specific that it has even been postulated that this lipid might behave as a real membrane receptor . However, although it is quite obvious that their natural function must be related to defence and/or predation, and although they have been shown to be lethal to some small crustaceans, molluscs and fish , their natural specific targets are not really known yet at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…6A) using gene-specific primers targeting the Crassicorin-Icoding region. Moreover, previous immunohistochemical and cytobiochemical analyses of the mesenteries from sea anemones demonstrated intense staining of cnidocytes and potent antimicrobial properties [44,45], suggesting that the mesenteries play an important role in production of immune-effector molecules in sea anemones. The highest expression level of Crassicorin-I-precursor transcripts was detected in the mesenteries.…”
Section: Crassicorin-i Is Involved In the Defense Mechanism Against Imentioning
confidence: 85%